Optimizing postbiotic production through solid-state fermentation with Bacillus amyloliquefaciens J and Lactiplantibacillus plantarum SN4 enhances antibacterial, antioxidant, and anti-inflammatory activities - Tong, Yucui; Guo, He'nan; Abbas, Zaheer; Zhang, Jing; Wang, Junyong; Cheng, Qiang; Peng, Shuyue; Yang, Tiantian; Bai, Ting; Zhou, Yichen; Li, Jinzhuan; Wei, Xubiao; et al. (Frontiers in Microbiology, 2023)
Postbiotics are an emerging research interest in recent years and are fairly advanced compared to prebiotics and probiotics. The composition and function of postbiotics are closely related to the fermentation conditions. In this study, we developed a solid-state fermentation preparation method for postbiotics with antimicrobial, antioxidant, and anti-inflammatory activities. The antibacterial activity was improved 3.62 times compared to initial fermentation conditions by using optimization techniques such as single factor experiments, Plackett-Burman design (PBD), steepest ascent method (SAM), and central composite design (CCD) methods. The optimized conditions were carried out with an initial water content of 50% for 8 days at 37°C, and fermentation strains of Bacillus. amyloliquefacuens J and Lactiplantibacillus. plantarum SN4 at a ratio of 1:1 with a total inoculum size of 8 %. The optimized SSF medium content ratio of peptide powder, wheat bran, corn flour, and soybean meal were 4%, 37.4%, 30%, and 28.6%. Under these optimized conditions, postbiotics with a concentration of 25 mg/mL showed significant broad-spectrum antibacterial capabilities against Escherichia. coli, Salmonella, and S.aureusStaphylococcus aureus etc., and strong antioxidant activity against ABTS, DPPH, and OH radicals. Moreover, the optimized postbiotics exhibited good anti-inflammatory ability for reducing nitric oxide (NO) secretion in RAW 264.7 macrophage cells in response to LPS-induced inflammation. Furthermore, the postbiotics significantly improved intestinal epithelial wound healing capabilities after mechanical injury, such as cell scratches in IPEC-J2 cells (p < 0.05). In brief, we developed postbiotics through optimized solid-state